The number and cycle of rat vibrissae according to topographic arrangement. (September 2014) - Kim, Jeong-Nam; Kim, Soo-Young; Lee, Ju-Young; Shin, Kang-Jae; Gil, Young-Chun; Koh, Ki-Seok; Song, Wu-Chul
Abstract This study investigated the cycle of rat vibrissae by counting their number relative to their topographic arrangement. The average duration of maintaining single or double vibrissal shafts was analyzed. The ratio of the lifetime of the single and double shafts was around 3:2 weeks. The rostral and caudal vibrissae had relatively short and long cyclic durations, respectively; this difference may be related to their length and function.